TEST-TAKING STRATEGICNESS IN OPEN BOOK TESTS - Suprihadi Suprihadi; Thomas Baharuddin Assyarofi (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
Perception about testing and preparation to take a test is usually actualized in what the students do before, during, and after testing. This research involves 50 students and 17 lecturers as respondents, and uses structured questionnaire as its instrument. The results of the analysis show that: 1) the test-taking strategy used by the students of Education Department, the University of Muria Kudus (EED UMK) in open book tests is fair, 2) inÂ Î± .01 and df 15, there is a significant dependency relationship between students grade and test-taking strategy use in open book tests although there is no exact relationship nature between these two variables.